2018
DOI: 10.1387/ijdb.170325ct
|View full text |Cite
|
Sign up to set email alerts
|

Chick midgut morphogenesis

Abstract: The gastrointestinal tract is an essential system of organs required for nutrient absorption. As a simple tube early in development, the primitive gut is patterned along its anterior-posterior axis into discrete compartments with unique morphologies relevant to their functions in the digestive process. These morphologies are acquired gradually through development as the gut is patterned by tissue interactions, both molecular and mechanical in nature, involving all three germ layers. With a focus on midgut morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 113 publications
(149 reference statements)
3
17
0
Order By: Relevance
“…This relationship between the initial growth stretch and number of ridges was in agreement with actual intestinal morphogenesis (Shyer et al 2013;Huycke and Tabin 2018).…”
Section: Energy Landscape Of Luminal Folding Caused By Growth and Consupporting
confidence: 86%
See 1 more Smart Citation
“…This relationship between the initial growth stretch and number of ridges was in agreement with actual intestinal morphogenesis (Shyer et al 2013;Huycke and Tabin 2018).…”
Section: Energy Landscape Of Luminal Folding Caused By Growth and Consupporting
confidence: 86%
“…As a realistic biological application, we applied the energy landscape approach to the morphogenesis of intestinal villus in vertebrates. In the initial stage of villus formation, the intestinal tube folds into longitudinal ridges with differential growth of the inner epithelial and mesenchymal layers, which is constrained by the outer circumferentially oriented muscle layer (Shyer et al 2013;Huycke and Tabin 2018). We performed FEAs for luminal folding of intestinal tube following previously reported analyses (Shyer et al 2013;Goriely 2017).…”
Section: Simulation Conditionsmentioning
confidence: 99%
“…12 b). 120 , 121 ) It has been suggested that two types of cellular changes in and around the dorsal mesentery are responsible for this leftward tilt. 121 , 122 ) First, mesenchymal cells of the right half of the dorsal mesentery become dispersed, whereas those of the left half become compacted.…”
Section: Asymmetric Organogenesismentioning
confidence: 99%
“…The gastrointestinal tract is an essential system of organs for animal growth because it performs vital functions in nutrient digestion and absorption ( Huycke and Tabin, 2018 ). Although the development of the intestine, a precise and ordered process, occurs through incubation, the functional abilities do not begin to develop until amniotic fluid is orally consumed by the chick embryo during the late incubation period.…”
Section: Introductionmentioning
confidence: 99%